A rapid and sensitive High-Performance Liquid Chromatography method with fluorescence detection for quantification of melatonin in small volume rat plasma samples: application to a preclinical study to determine the oral pharmacokinetics of melatonin under gestational conditions (Brazilian Journal of Pharmaceutical Sciences, 2024)
A novel, simple and sensitive high-performance liquid chromatography with fluorescence detection method was developed and validated for the characterization of the preclinical pharmacokinetics of melatonin under pregnant conditions. Plasma samples (25 µL) were treated with 30 µL of ethanol absolute (containing the internal standard, IS). After a centrifugation process, aliquots of supernant (5 µL) were injected into the chromatographic system. Compounds were eluted on a Xbridge C18 (150 mm x 4.6 mm i.d., 5 µm particle size) maintained at 30°C. The mobile phase consisted in a mixture of aqueous solution of 0.4% phosphoric acid and acetonitrile (70:30 v/v). The wavelengths were set at 305 nm (excitation) and 408 nm (emission) and the total analysis time was 8 min/sample. All validation tests were obtained with accuracy and precision, according to FDA guidelines, over the concentration range of 0.005-20 µg/mL. Pharmacokinetic study showed that melatonin systemic exposure increased from day 14, with a significant difference at 19 days of gestation compared to the control group. Our findings suggest a decreased metabolism of melatonin as result of temporary physiological changes that occur throughout pregnancy. However, other maternal physiological changes cannot be ruled out.